Shari’ah issues, challenges, and prospects for Islamic derivatives: a qualitative study - Sakti, M. R. P. (Emerald Group Publishing Ltd., 2016)
Purpose: The purpose of this study is to investigate shari’ah scholars’ views and experiences pertaining the shari’ah issues, challenges and prospects in Islamic derivatives. Specifically, this paper critically examines the criticisms toward conventional derivative instruments and the controversies surrounding underlying contracts and current Islamic derivative products. Design/methodology/approach: This study uses qualitative methods to form a deeper understanding of shari’ah scholars’ perception and experience on Islamic derivatives. Semi-structured interviews were conducted with five shari’ah scholars who are currently working in Islamic financial institutions in Malaysia and Singapore. This study used phenomenological techniques for its data analysis. Findings: This study has found that shari’ah scholars are aware of the shari’ah issues surrounding Islamic derivatives and have provided comprehensive insight on the solution to these issues. It was found that it is important to take into account the derivatives instruments in Islamic financial industry because of the need for hedging and risk mitigation within Islamic financial institutions. Nonetheless, the study has also found that the use of wa’ad contracts to structure Islamic profit rate swaps and foreign currency exchanges are problematic because of it having features of bay’ al-kali’ bil-kali (the sale of one debt for another). Originality/value: This study is one of few studies that highlight the shari’ah issues of Islamic derivatives in Islamic banking and finance industry. This paper is of value in discussing risk management and Islamic derivatives in Islamic financial institutions and how there are many issues under the investigation process, particularly issues related to controversial underlying contracts and products.